The Effect of Autophagy on Chronic Intermittent Hypobaric Hypoxia Ameliorating Liver Damage in Metabolic Syndrome Rats - Cui, Fang; Hu, Hao Fei; Guo, Jing; Sun, Jie; Shi, Min (Frontiers in Physiology, 2020)
Aim: Our previous study demonstrated that chronic intermittent hypobaric hypoxia (CIHH) can confers hepatic protection by reducing endoplasmic reticulum stress (ERS) in high-fat-high-fructose induced metabolic syndrome (MS) rats. It is known that there is a functional coupling between autophagy and ERS. This study aimed to investigate the effect of CIHH on autophagy function and adenosine mono-phosphate-activated protein kinase-mammalian target of rapamycin (AMPKα-mTOR) signaling pathway in hepatic tissue of MS rats. Main methods: Adult male Sprague-Dawlay rats were randomly divided into: control (CON), CIHH (treated with hypobaric hypoxia simulating 5000-m altitude for 28 days, 6 hours daily), MS (induced by high fat diet and 10% fructose water feeding for 16 weeks), and MS+CIHH groups. Body weight, Lee's index, fat coefficient, systolic arterial pressure, blood biochemicals, and histopathology of liver were measured, the expression of phosphor (p)-AMPKα, p-mTOR, autophagy-related and ERS-related proteins were assayed in hepatic tissue. Key findings: The MS rats displayed obesity, hypertension, hyperglycemia, hyperlipidemia, hepatic tissue morphological and functional damage, and the up-regulated expressions of ERS-related, autophagy-related proteins and p-mTOR, and the down-regulated expression of p-AMPKα. All aforementioned abnormalities in MS rats were ameliorated in MS+CIHH rats. Significance: In conclusion CIHH confers hepatic protection through activating AMPKα-mTOR signaling pathway and the autophagy function, thus inhibiting ERS in hepatic tissue.